DIVERSITY ANALYSIS AND IDENTIFICATION OF PROMISING LINES FOR HYBRIDIZATION IN FIELD PEA (PISUM SATIVUM L.) - SAXESENA, RAVI RANJAN; G. M. LAL; S. YADAV, PUNAM; K. VISHWAKARMA, MANISH (The Bioscan, 2013)
In the present study, twenty one advanced breeding lines and two varieties (HUDP 15 and IPFD 1-10) as check were evaluated for assessing genetic divergence for exploitation in a breeding programme aimed at improving yield potential of field pea by using Mahalanobis D2 statistics. The intra-cluster D2 value ranged from 0.00 to 65.10 while inter-cluster D2 value ranged from 101.389 to 763.200 indicated that the selected advance breeding lines were highly divergent. The maximum intra cluster distance was recorded for cluster I (65.109) while cluster IV and V (0.00) showed no intra-cluster distance values revealed homogenous nature of the genotype within the cluster. The genetically more divergent advanced breeding lines present in cluster II and V as indicated by intercluster distance value (763.200). Selecting lines of these clusters probably provide promising recombinants and better segregants for future breeding programme.